Expectation Gap: Do Companies Disclose What Users Need in Iran? - Soheila Mirshekary (Journal of Accounting, Business and Management (JABM), 2005)
This paper reports the results of two empirical research studies including the needs and requirements of the users of financial reports and the current corporate financial disclosure practices in Iran. It uses the results of two separate surveys and compares users perceptions about the information items which are currently disclosed in Iranian corporate annual reports with the current corporate disclosures by Iranian companies listed on TSE. To discover to what extent the Iranian financial practices disclose users expectations, Spearman Rank correlation coefficients were used to compare the mean rank of user group perception and the mean rank of actual disclosure for each section of annual reports and overall disclosure separately. This research investigates informational efficiency and determines the extent of financial disclosure by a set of Iranian corporations and compares this to the level desired by different users. The objective of this survey is to find the degree of consensus between actual disclosure and users information needs